Know your right at work [ (Video Education Australasia, 2000)
For students joining the labour force, knowledge of basic employment rights is essential. Topics explored here include: contracts, salary, hours, superannuation, new apprenticeships & traineeships, discrimination, harassment, violence, safety, unfair dismissal